Generation and Staging of Human Retinal Organoids Based on Self-Formed Ectodermal Autonomous Multi-Zone System - Li, Jinyan; Chen, Yijia; Ouyang, Shuai; Ma, Jingyu; Sun, Hui; Luo, Lixia; Chen, Shuyi; Liu, Yizhi (Frontiers in Cell and Developmental Biology, 2021)
Methods for stem cell-derived, three-dimensional retinal organoids induction have been established and shown great potential for retinal development modeling and drug screening. Herein, we reported an exogenous-factors-free and robust method to generate retinal organoids based on “self-formed ectodermal autonomous multi-zone” (SEAM) system, a two-dimensional induction scheme that can synchronously generate multiple ocular cell lineages. Characterized by distinct morphological changes, the differentiation of the obtained retinal organoids could be staged into the early and late differentiation phases. During the early differentiation stage, retinal ganglion cells, cone photoreceptor cells (PRs), amacrine cells, and horizontal cells developed; whereas rod PRs, bipolar cells, and Müller glial cells were generated in the late differentiation phase, resembling early-phase and late-phase retinogenesis in vivo. Additionally, we modified the maintenance strategy for the retinal organoids and successfully promoted their long-term survival. Using 3D immunofluorescence image reconstruction and transmission electron microscopy, the substantial mature PRs with outer segment, inner segment and ribbon synapse were demonstrated. Besides, the retinal pigment epithelium (RPE) was induced with distinct boundary and the formation of ciliary margin was observed by co-suspending retina organoids with the zone containing RPE. The obtained RPE could be expanded and displayed similar marker expression, ultrastructural feature and functional phagocytosis to native RPE. Thus, this research described a simple and robust system which enabled generation of retina organoids with substantial mature PRs, RPE and the ciliary margin without the need of exogenous factors, providing a new platform for research of retinogenesis and retinal translational application.